UTILIZAREA OPTIMĂ A RESURSELOR PUBLICITARE - Gribincea, Alexandru; Bejan, Oxana; Barbacaru, Elena; Prodan, Marina (CEP USM, 2010)
Advertising is a form of communication used to influence individuals to purchase products or services or support political candidates or ideas. Frequently it communicates a message that includes the name of the product or service and how that product or service could potentially benefit the consumer. Advertising often attempts to persuade potential customers to purchase or to consume a particular brand of product or service. Modern advertising developed with the rise of mass production in the late 19th and early 20th centuries. Commercial advertisers often seek to generate increased consumption of their products or services through branding, which involves the repetition of an image or product name in an effort to associate related qualities with the brand in the minds of consumers. Different types of media can be used to deliver these messages, including traditional media such as newspapers, magazines, television, radio, billboards or direct mail. Advertising may be placed by an advertising agency on behalf of a company or other organization.
Keywords: utilizarea publicităţii; resursele publicitare